Using SBIRT (Screen, Brief Intervention, and Referral Treatment) Training to Reduce the Stigmatization of Substance Use Disorders Among Students and Practitioners - Efren Gomez; Matthew Gyger; Stephanie Borene; Amanda Klein-Cox; Ramona Denby; Sara Hunt; Oscar Sida (SAGE Publishing, 2023)
Negative attitudes and stigmatization of substance-using patients lead to treatment avoidance and poor physical and health outcomes. Research suggests that training in substance use disorders is a vital tool to abate negative attitudes among health workers. The present longitudinal study trained students and experienced practitioners from various disciplines on the evidence-based Screening, Brief Intervention, and Referral to Treatment (SBIRT) model. The study found significant improvements in the attitudes of students-but not practitioners-who were trained during the program. The paper discusses policy and implementation implications to support and complement sustained impact of training on models such as SBIRT.